Adult and offspring size in the ocean: a database of size metrics and conversion factors. Issue 4 (April 2016) - Neuheimer, Anna B.; Hartvig, Martin; Heuschele, Jan; Hylander, Samuel; Kiørboe, Thomas; Olsson, Karin H.; Sainmont, Julie; Andersen, Ken H.
Abstract: The purpose of this dataset was to compile adult and offspring size estimates for marine organisms. Adult and offspring size estimates of 408 species were compiled from the literature covering >17 orders of magnitude in body mass and including Cephalopoda (ink fish), Cnidaria ("jelly" fish), Crustaceans, Ctenophora (comb jellies), Elasmobranchii (cartilaginous fish), Mammalia (mammals), Sagittoidea (arrow worms) and Teleost (i.e., Actinopterygii, bony fish). Individual size estimates were converted to standardized size estimates (carbon weight, g) to allow for among‐group comparisons. This required a number of size estimates to be converted and a compilation of conversion factors obtained from the literature are also presented.